Antifibrotics in COVID-19 Lung Disease: Let Us Stay Focused - Chaudhary, Sachin; Natt, Bhupinder; Bime, Christian; Knox, Kenneth S.; Glassberg, Marilyn K. (Frontiers in Medicine, 2020)
After decades of research, two therapies for chronic fibrotic lung disease are now FDA approved with dozens more anti-fibrotic therapies in the pipeline. A great deal of enthusiasm has been generated for use of these drugs, which are by no means curative, but clearly have a favorable impact on lung function decline over time. Amidst a flurry of newly developed drugs/antibodies and repurposed drugs to treat COVID-19 disease and accompanying ARDS, none have emerged as winners. Historically, survivors of severe viral pneumonia and related acute lung injury with ARDS often have near full recovery of lung function. However, in COVID-19, highly publicized cases of lung transplantation for organ failure related to COVID-19 have emerged. While the pathological findings of the lungs of patients with COVID-19 can be diverse, current reports have not shown lung fibrosis to a significant degree. A recent call on social media implicates the institution of preventative therapy for inevitable lung fibrosis. In fact, clinical trials are underway using currently FDA approved anti-fibrotic therapies. This perspective focuses on the relatively favorable outcomes of survivors of virus-mediated ARDS, the low prevalence of clinically meaningful lung fibrosis in survivors and argues against the proliferation of studies aimed to bend the curve of COVID-19 associated lung fibrosis.